INFLUENCE OF AMMONIUM PYRROLIDINEDITHIOCARBAMATE ADMINISTRATION ON THE DEVELOPMENT OF OXIDATIVE STRESS IN RAT HEART ON THE BACKGROUND OF METABOLIC SYNDROME MODELING - Akimov, O.Y.; Mykytenko, A.O.; Kostenko, V.O.; Yeroshenko, G.A. (World of Medicine and Biology, 2024)
Metabolic syndrome, despite being a disease of non-infectious origin, is often accompanied by inflammation induced by metabolic disorders (meta-inflammation). The purpose of this work is to determine the activity of antioxidant enzymes, the production of superoxide anion radical, the content of oxidatively modified proteins and the concentration of malondialdehyde in the heart of rats under conditions of experimental metabolic syndrome and ammonium pyrrolidine dithiocarbamate administration. The study was conducted on 24 mature male Wistar rats weighing 200-260 g. The animals were divided into 4 groups of 6 animals each: control group; metabolic syndrome group (metabolic syndrome was reproduced by using a 20 % fructose solution as the only source of water for 60 days); ammonium pyrrolidinedithiocarbamate administration group (i.p. 76 mg/kg thrice a week for 60 days), and group of ammonium pyrrolidinedithiocarbamate administration on the background of metabolic syndrome modeling. Metabolic syndrome leads to development of oxidative stress in rat heart, which is characterized by excessive production of reactive oxygen species and insufficiency of antioxidant defense. Ammonium pyrrolidine dithiocarbamate administration decreased superoxide production by 55.44 %, increased superoxide dismutase and catalase activity by 156.32 % and 111.44 %, respectively, and decreased concentration of malondialdehyde by 22.41 %. Administration of blocker of NF-κB activation (ammonium pyrrolidinedithiocarbamate) during modeling of metabolic syndrome limits excessive production of reactive oxygen species and intensity of lipid peroxidation, while increasing antioxidant defense of rat heart.
Keywords: metabolic syndrome; heart; NF-κB; ammonium pyrrolidinedithiocarbamate; oxidative stress